Developing rock ramp fishway criteria for fishes of regional conservation concern - Paik, Kira, author; Myrick, Christopher A., advisor; Kanno, Yoichiro, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2024)
Rivers and streams in the United States have been greatly fragmented by the construction of instream structures such as dams, diversions, and culverts to meet the growing needs of human populations. Many of these structures inhibit upstream movement by fish species, negatively affecting abundance as well as overall survival. Conservation efforts are looking at restoring connectivity through the installation of fish passage structures or fishways. To improve effectiveness and functionality of these fish passage structures, the swimming abilities of the target species should be considered when creating the design. Rock ramp fishways are becoming increasingly utilized because they can allow passage of a large assortment of species with variable swimming abilities and are highly customizable. Creating cast concrete fishways in this style can also help to reduce the cost of construction of passage structures. We evaluated the passage success of five fish species of conservation concern using an experimental rock ramp fishway at slopes of 2-10%, in 2% increments. This study focused on species of national or regional conservation concern including Topeka Shiner Notropis topeka, Suckermouth Minnow Phenacobius mirabilis, Rio Grande Chub Gila pandora, Rio Grande Sucker Catostomus plebeius, and Mottled Sculpin Cottus bairdii. Our results showed that decreased slope and distances would lead to higher passage success for the five species. For the entire length of the fishway (6.1 m), all species had very high passage probabilities (> 0.9) at the lowest slopes 2 and 4%, and for all species except the Topeka Shiner, the 6% slope also had high passage probabilities (> 0.8). At 8% and 10% slopes, passage success for these species decreased drastically (< 0.31) and would not be recommended for longer fishways (> 2.03 m between resting areas). Based on these results, managers designing fishways for these species should be able to pick ideal combinations of slope and length to successfully allow passage of an acceptable proportion of the fish to attain management goals.
Keywords: rock ramp fishway; fish passage